Is "Response/No Response" Too Simple a Notion for RTI Frameworks? Exploring Multiple Response Types With Latent Profile Analysis. (November 2020) - Peng, Peng; Fuchs, Douglas; Fuchs, Lynn S.; Cho, Eunsoo; Elleman, Amy M.; Kearns, Devin M.; Patton, Samuel; Compton, Donald L.
We conducted a secondary analysis of data from a randomized control trial to explore this question: Does "response/no response" best characterize students' reactions to a generally efficacious first-grade reading program, or is a more nuanced characterization necessary? Data were collected on 265 at-risk readers' word reading prior to and immediately following program implementation in first grade and in spring of second grade. Pretreatment data were also obtained on domain-specific skills (letter knowledge, decoding, passage comprehension, language) and domain-general skills (working memory, non-verbal reasoning). Latent profile analysis of word reading across the three time points with controls as a local norm revealed a strongly responsive group ( n = 45) with mean word-reading z scores of 0.25, 1.64, and 1.26 at the three time points, respectively; a mildly responsive group ( n = 109), z scores = 0.30, 0.47, and 0.55; a mildly non-responsive group ( n = 90), z scores = −0.11, −0.15, and −0.55; and a strongly non-responsive group ( n = 21), z scores = −1.24, −1.26, and −1.57. The two responsive groups had stronger pretreatment letter knowledge and passage comprehension than the two non-responsive groups. The mildly non-responsive group demonstrated better pretreatment passage comprehension than the strongly non-responsive group. No domain-general skill distinguished the four groups. Findings suggest response to early reading intervention was more complicated than response/no response, and pretreatment reading comprehension was an important predictor of response even with pretreatment word reading controlled.